Pengembangan Usaha Kue Bolu Coklat Brownies Sq-Five - Maylti Rante Pala; Selin Bessoran Palulun; Ayu Prastika; Enjelin Kondorura; Yohanis Lotong Ta’dung (Jurnal Pengabdian Kepada Masyarakat, 2022)
Dessert boxes are one of the dessert (cake) snack products that are currently in great demand among consumers. Sweet foods arranged in transparent boxes usually consist of several layers. such as sponge cake, sweet cream, a pinch of cocoa powder, dry cakes as decoration. The aim of this business is to gain experience by learning entrepreneurship while making a profit, giving motivation to the young generation of Indonesia to always have ideas to produce a product that has value. benefits for himself and the community, enlivening the culinary variety. add to the creation of a special food menu, the raw materials used are easy to get. And the aim is to find out the current financial condition of the business or business and to see the impact of the business on the community economy together.